Calendars of M. Pochobutas - Budinaitė, Salomėja (Knygotyra, 1987)
In the fourties of the XVIII century the publishing house of the Academy of Vilnius began to print political and historical calendars. Reforms in calendar made J. Poshakovskis. His work was continued by P. Paprockis and M. Pochobutas. M. Pochobutas published “Vilnius’ calendar” from 1774 till 1795. He completely changed the contents of the calendar. In the article structure and destination of calendars is analysed. In calendars besides the usual calendar information the editor inserted bits of historical, political, geographical, astronomical, economical information, official documents, material from sessions of the parliament. M. Pochobutas began to publish scientific articles, data about observations of the Vilnius Astronomy Observatory.In 1787 M. Pochobutas published a new calendar – “Academical calendar”, which was devoted to education and science problems in Lithuania.Calendars of M. Pochobutas partly played the role of periodicals, they were a source of information presented, the science achievements.